Pembinaan Strategi Sosialisasi Seni Teater Tradisi Sandur Kepada Masyarakat Melalui Media Sosial Dalam Gaya Pertunjukan Di Sanggar Sedhet Srepet - lestari, lilis; hari pramono, koko; mestikasari, ratna; fidaus, mujib (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
In accordance with the purpose of community service, this PkM activity is oriented to restore the community's interest and enthusiasm for traditional theater arts through coaching and mentoring with material on the strategy of socializing traditional sandur theater arts to the community through social media in the performance style at the Sedhet Srepet Studio. The phenomenon found in the community is that the next generation of traditional theater art activists is decreasing due to the lack of information and education from families, schools to the scope of electronic media and the onslaught of modern culture that shifts the character of the younger generation. This problem encouraged the author to carry out this activity to be able to encourage and assist traditional theater art practitioners so that they can regenerate and increase public interest in this art so that it is not eroded by modern culture from outside. This PkM activity program is carried out using the Training and Capacity Building method through the Service Learning approach through the application of technology and innovation. The results of this PkM activity program concluded that the optimization of the traditional theater performance style based on the need to maximize innovation in traditional theater performances so that they are in accordance with the context of development and the needs of the times and can adapt according to the needs of this performance. The Sanggar Sedhet Srepet Team has effectively used social media on Instagram and Youtube and in the future will be added other social networking accounts, because by utilizing these media it is considered to have been able to increase the enthusiasm of the Bojonegoro community to enjoy the performance. Instagram media has proven to be able to introduce theater arts well to the Instagram user community, this is evident from the existence of several followers who are interested in watching and studying theater arts and are interested in joining the community on the Instagram account @sandur_sedhet_srepet.